In Vitro Resistance Studies with Bacteria That Exhibit Low Mutation Frequencies: Prediction of “Antimutant” Linezolid Concentrations Using a Mixed Inoculum Containing both Susceptible and Resistant Staphylococcus aureus - Firsov, Alexander A. (Antimicrob Agents Chemother, 2015)
Bacterial resistance studies using in vitro dynamic models are highly dependent on the starting inoculum that might or might not contain spontaneously resistant mutants (RMs). To delineate concentration-resistance relationships with linezolid-exposed Staphylococcus aureus, a mixed inoculum containing both susceptible cells and RMs was used. An RM selected after the 9th passage of the parent strain (MIC, 2 μg/ml) on antibiotic-containing media (RM9; MIC, 8 μg/ml) was chosen for the pharmacodynamic studies, because the mutant prevention concentration (MPC) of linezolid against the parent strain in the presence of RM9 at 10(2) (but not at 10(4)) CFU/ml did not differ from the MPC value determined in the absence of the RMs. Five-day treatments with twice-daily linezolid doses were simulated at concentrations either between the MIC and MPC or above the MPC. S. aureus RMs (resistant to 2× and 4× MIC but not 8× and 16× MIC) were enriched at ratios of the 24-h area under the concentration-time curve (AUC(24)) to the MIC that provide linezolid concentrations between the MIC and MPC for 100% (AUC(24)/MIC, 60 h) and 86% (AUC(24)/MIC, 120 h) of the dosing interval. No such enrichment occurred when linezolid concentrations were above the MIC and below the MPC for a shorter time (37% of the dosing interval; AUC(24)/MIC, 240 h) or when concentrations were consistently above the MPC (AUC(24)/MIC, 480 h). These findings obtained using linezolid-susceptible staphylococci supplemented with RMs support the mutant selection window hypothesis. This method provides an option to delineate antibiotic concentration-resistance relationships with bacteria that exhibit low mutation frequencies.